Perbandingan Hasil Belajar Peserta Didik dalam Penggunaan Metode Bermain Peran - Silvia, Ninda; Ropida, Ilyani; Fadilah, Agus; Supriyadi, Muhamad Andri (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: Knowing the comparison of student learning outcomes using the role-playing method. Methodology: This research is a type of quantitative research. The research design uses a One-Shot Case Study design. The data collection instrument used was multiple choice questions. Data analysis uses descriptive statistics to analyze data by describing or describing the data that has been collected. Main Findings: Learning outcomes obtained by students are produced from excellent and correct role-playing methods. Novelty/Originality of this Research: This research has novelty or something different from other studies, namely using role-playing methods that are integrated into learning activities to obtain good learning outcomes.